Pengaruh Penggunaan Ps Ball sebagai Pengganti Pasir terhadap Kuat Lentur Beton - Simatupang, Ronald; Pratiwi, Prasthi Aldri (Zenit, 2013)
Global warming is becoming worse; therefore, innovation and creativity are needed to minimize global warming effects. One of the innovation and creativity can replace material inconcrete mixing with waste material. Waste material used in this research is steel production waste, named Precious Steel Ball (PS Ball). PS Ball is used in this research to replace fine aggregate with PS Ball, whose percentage addition of PS Ball is 0%, 5%, 10%, 15% to 50% as a replacement for of thevolume of fine aggregate. Specimen used to study the beam flexural strength of concrete is the size of 600 x 150 x 150 mm. The results shows that the maximum flexural strength in the mixture without using PS Ball with flexural strength values is obtained at 4.254 MPa. While the flexural strength witha mixture of sand instead of PS Ball can lower flexural strength by an average of 27.341% compared to the concrete mix without the use of PS Ball. The pattern of cracks occurs in the concrete without bending mixture of PS Ball and Ball PS percentage of the mixture is up to 30% and 45%. The patternof bending and shear cracks occurs at the levels of PS Ball 35%, 45% and 50%.Keywords: PS. Ball, flexural strength, concrete beam